Stereotactic Body Radiation Therapy (SBRT) Improves Local Control and Overall Survival Compared to Conventionally Fractionated Radiation for Stage I Non-Small Cell Lung Cancer (NSCLC) - von Reibnitz, Donata (Acta Oncol, 2018)
BACKGROUND: Stereotactic Body Radiotherapy (SBRT) has been adopted as the standard of care for inoperable early-stage non-small cell lung cancer (NSCLC), with local control rates consistently > 90%. However, data directly comparing the outcomes of SBRT with those of conventionally fractionated radiotherapy (CONV) is lacking. MATERIAL AND METHODS: Between 1990 and 2013, 497 patients (525 lesions) with early-stage NSCLC (T1-T2N0M0) were treated with CONV (n=127) or SBRT (n=398). In this retrospective analysis, five endpoints were compared, with and without adjusting for clinical and dosimetric factors. Competing risks analysis was performed to estimate and compare the cumulative incidence of local failure (LF), nodal failure (NF), distant failure (DF) and disease progression. Overall survival (OS) was estimated by the Kaplan-Meier method and compared by the Cox regression model. Propensity score (PS) matched analysis was performed based on seven patient and clinical variables: age, gender, Karnofsky performance status (KPS), histology, T-stage, biologically equivalent dose (BED), and history of smoking. RESULTS: The median dose delivered for CONV was 75.6 Gy in 1.8 to 2.0 Gy fractions (range 60 to 90 Gy; median BED = 89.20 Gy) and for SBRT 48 Gy in 4 fractions (45 to 60 Gy in 3 to 5 fractions; median BED = 105.60 Gy). Median follow up was 24.4 months, and 3-year LF rates were 34.1% with CONV and 13.6% with SBRT (p<0.001). 3-year OS rates were 38.9% and 53.1%, respectively (p=0.018). PS matching showed a significant improvement of OS (p=0.0497) for SBRT. T-stage was the only variable correlating with all five endpoints. CONCLUSION: SBRT compared to CONV is associated with improved LF rates and OS. Our data supports the continued use and expansion of SBRT as the standard of care treatment for inoperable early-stage NSCLC.